Determinants of foreign direct investment in Malaysia / Nur Luqman Hadee Dahalan and Nurliyana Nabilah Rosly - Dahalan, Nur Luqman Hadee; Rosly, Nurliyana Nabilah (Faculty of Business and Management, 2019)
The development and the economic growth of one country are depending on the foreign direct investment. Foreign direct investment is one of an extremely important role of a country. Most of the developing countries are rely on the foreign direct investment to expose their country economy as they face lack of capital in their developing process. Foreign direct investment bring out capitals, technology and skills into the developing countries that immediately helping to satisfy country’s need. In Malaysia growth performance, it really depends on foreign direct investment. It generates the economic growth by increasing the capital formation which include production capacity, export growth and employment in Malaysia. Foreign direct investment inflows in Malaysia fluctuate in 1996 until 2010 and the volatility of foreign direct investment inflows drew questions to the researcher regarding the factors affecting foreign direct investment decision in Malaysia by annual time series data from 1986 until 2017. The dependent variables and independent variables are applied to the multiple regression model to examine the relation between both variables. All independent variables are significantly and have the positive affect in the foreign direct investment inflows except one of the independent variables. Further explanation regarding the one independent variables that are failed to be significant relationship with foreign direct investment inflows.